Economic inequality and poverty : Facts, methods, and policies - Kakwani, Nanak; Son, Hyun H. (Oxford, United Kingdom : Oxford University Press, 2022)
c
1 Introduction -- 2 Income distributions -- 3 The Lorenz curve and its variants -- 4 Welfare ranking of income distributions -- 5 Measurement of income inequality -- 6 Specifying poverty lines -- 7 Poverty measures -- 8 Multi-dimensional poverty -- 9 The concentration curves -- 10 Applications of concentration curves to economic analysis -- 11 Tax progressivity and redistribution effect of taxes -- 12 Normative measures of tax progressivity -- 13 Negative income tax plans -- 14 Targeting tools to evaluate social programs -- 15 Social price indices and inequality -- 16 Poverty price indices -- 17 Economic growth and poverty -- 18 Pro-poor growth.
Includes bibliographical references (pages [480]-491) and indexes.
Keywords: Income distribution -- Mathematical models; Equality -- Economic aspects; Poverty -- Economic aspects; Income distribution; Income distribution -- Mathematical models; Economic Development; Economic Growth